Beginning Photo Retouching and Restoration Using GIMP - Whitt, Phillip; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2014)
Beginning Photo Retouching & Restoration Using GIMP teaches the reader how to achieve professional results using this high end image editor. You'll learn how to do everything from making dull images "pop" to resurrecting badly damaged photographs deemed beyond any hope of rescue. There's no need to shell out good money month after month for the "big name" software package. GIMP 2.8 is a world-class image editor that wields almost as much power, and is completely free! Learning the art of photo retouching and restoration is fun and rewarding. Reclaim those treasured images from the ravages of time and neglect, and pass them on to future generations. Beginning Photo Retouching & Restoration Using GIMP will provide you with a wide array of editing exercises to help you develop a high degree of proficiency. Whether you are the designated "family archivist" wanting to preserve your family history, or a professional photographer with a desire to add an extra revenue generating service, this book will be an invaluable aid. • Shows how to acquire the best scans and digitize large photographs. • Teaches you how to digitally repair damaged prints, correct color shifts, reclaim lost detail-even colorize black and white images. • Offers great tips on how to maintain and preserve your newly printed restored photographs, and how to properly store originals.
Keywords: Computer graphics; Multimedia systems .; Computer Graphics; Media Design